Political Impact of Research - Rodrigues de Oliveira, Cintia; Paes Barreto Davel, Eduardo (Organizações & Sociedade, 2021)
Discussions on political impact broaden our understanding of the impact of academic research and deepen our awareness of underlying and socially constructed dynamics that determine the very meaning of what will be collectively understood as impact. Three major types of impact can be considered when discussing how researchers can fully observe the political impact of their research: (a) promotion of emancipation and critical thinking, (b) promotion of debates on the public interest and (c) contribution of the study results to the process of denaturalizing knowledge considered as neutral. The political impacts of academic research represent the future development of societies and organizations, as they make life viable in a collective, social and democratic context. If so, why are we still unable to substantiate, enable and operationalize such consideration into our scientific research metrics and guidelines?